Da Sørlandet ble Sørlandet - Hundstad, Dag (Tidsskrift for kulturforskning, 2016)
Abstract During the first decades of the 20th century, a strong regional identity was constructed in the Sørlandet region. This is the southernmost region of Norway and consists of the coun-ties of Aust-Agder and Vest-Agder. The name "Sørlandet" was introduced by the poet and region builder Vilhelm Krag in 1902. The regionalists aimed at making the culture of the region more visible in a national context, but they also worked for other causes, such as to improve the communications with the capital and to develop tourism. In the 1930s, strong regional symbols and images were constructed, in close connection with the current touristic promotion of Sørlandet as "the Riviera of Norway". The article discusses the different elements that were involved in constituting and promoting the regional iden-tity, such as media, different regional organizations, art, literature, popular songs and the tourism industry.